2020
DOI: 10.7717/peerj.9641
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of commercially important reef fishes in Weh Island, Aceh, Indonesia

Abstract: Knowledge on the precise identification of fish resources is critical for sustainable fisheries management. This study employs the DNA barcoding approach to generate a molecular taxonomic catalogue of commercially important reef fishes in the waters of Weh Island (Aceh Province), the most northerly inhabited island in the biodiverse Indonesian Archipelago. The waters not only support artisanal fisheries but also a feeder for the industry in the greater island of Aceh. In total, 230 specimens from 72 species be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 73 publications
(97 reference statements)
0
28
0
Order By: Relevance
“…These 20 studies comprised 39 species in six genera, especially the groupers, with high economic value. The studied genera were Anyperodon (Ariyanti and Farajallah, 2019a), Cephalopholis Andriyono and Suciyono, 2020;Ariyanti and Farajallah, 2019a;Ariyanti et al, 2015;Fadli et al, 2021;Fadli et al, 2020;Gaither et al, 2011;Kamal et al, 2019;Sari et al, 2015), Cromileptes (Nuryanto et al, 2018;Susanto et al, 2011;Susanto et al, 2010), Epinephelus (Abdullah and Rehbein, 2017; 193 Razi et al (2021) and Suciyono, 2020; Antoro et al, 2006;Farajallah, 2019a, 2019b;Aznardi and Madduppa, 2020;Fadli et al, 2021;Fadli et al, 2020;Jefri et al, 2015;Kamal et al, 2019;Kusuma, 2018;Nuryanto et al, 2018;Santosa et al, 2021;Sari et al, 2015;Yulidaria, 2020), Plectropomus (Fadli et al, 2021;Nuryanto et al, 2018), Variola (Abdullah and Rehbein, 2017;Fadli et al, 2021;Fadli, Nor, et al, 2020;Kamal et al, 2019;Sari et al, 2015) (Tabel 2). Genus Epinephelus being the highest percentage of the studied grouper (54%), and the lowest is from the genus Anyperodon (2%) (Figure 2, Table 1).…”
Section: Grouper Dna Barcoding Studies In Indonesiamentioning
confidence: 99%
See 3 more Smart Citations
“…These 20 studies comprised 39 species in six genera, especially the groupers, with high economic value. The studied genera were Anyperodon (Ariyanti and Farajallah, 2019a), Cephalopholis Andriyono and Suciyono, 2020;Ariyanti and Farajallah, 2019a;Ariyanti et al, 2015;Fadli et al, 2021;Fadli et al, 2020;Gaither et al, 2011;Kamal et al, 2019;Sari et al, 2015), Cromileptes (Nuryanto et al, 2018;Susanto et al, 2011;Susanto et al, 2010), Epinephelus (Abdullah and Rehbein, 2017; 193 Razi et al (2021) and Suciyono, 2020; Antoro et al, 2006;Farajallah, 2019a, 2019b;Aznardi and Madduppa, 2020;Fadli et al, 2021;Fadli et al, 2020;Jefri et al, 2015;Kamal et al, 2019;Kusuma, 2018;Nuryanto et al, 2018;Santosa et al, 2021;Sari et al, 2015;Yulidaria, 2020), Plectropomus (Fadli et al, 2021;Nuryanto et al, 2018), Variola (Abdullah and Rehbein, 2017;Fadli et al, 2021;Fadli, Nor, et al, 2020;Kamal et al, 2019;Sari et al, 2015) (Tabel 2). Genus Epinephelus being the highest percentage of the studied grouper (54%), and the lowest is from the genus Anyperodon (2%) (Figure 2, Table 1).…”
Section: Grouper Dna Barcoding Studies In Indonesiamentioning
confidence: 99%
“…Research on the Anyperodon genus Ariyanti and Farajallah (2019a) found that mitochondrial COI primers AF282, AF283 have successfully been used to identify the Anyperodon leucogrammicus species. Research on DNA barcoding in the genus Cephalopholis was carried out using different mitochondrial COI primers, including Fish F1, Fish R1 (Ariyanti et al, 2015;Fadli et al, 2021;Fadli et al, 2020); FH70, RH70 (Kamal et al, 2019) Fish BCL, Fish BCH Andriyono and Suciyono, 2020); 16SAR, 16SBR (Sari et al, 2015); AF282, AF283 (Ariyanti and Farajallah, 2019a) and has been reported to have identified several species in the genus Cephalopholis, namely: C. boenak, C. cyanostigma, C. formosa, C. leopardus, C. miniata, C. nigripinnis, C. sexmaculata, C. sonnerati, C. spiloparaea and C.urodeta. Further research on the genus Cromileptes using primers Fish F1, Fish R1 (Nuryanto et al, 2018); Fish F2, Fish R2 (Susanto et al, 2011;Susanto et al, 2010) have identified the species C. altivelis (Table 2).…”
Section: Grouper Dna Barcoding Studies In Indonesiamentioning
confidence: 99%
See 2 more Smart Citations
“…For fish, the research project Fish Barcode of Life Initiative (FISH-BOL), launched in 2005 [21], is probably the most important initiative that not only increased the amount of reference sequences on a global scale, but also provided laboratory protocols, alternative primer cocktails and suggestions to overcome failures [22,23]. Identification of fish species by DNA barcoding has been applied in several contexts [24][25][26][27] and has also been used to certificate the authenticity of fish species by detecting species substitution on commercial markets [9,[28][29][30]. Indeed, in the fields of seafood safety, DNA barcoding has earned itself a central role, demonstrating its potential for fast and reliable identification of frauds and is a valid method used by the US Food and Drug Administration for species identification of fish [31].…”
Section: Introductionmentioning
confidence: 99%